Quality and antioxidant response of gilthead seabream (Sparus aurata L.) to dietary supplements of fenugreek (Trigonella foenum graecum) alone or combined with probiotic strains. Issue 63 (April 2017) - Guardiola, F.A.; Bahi, A.; Messina, C.M.; Mahdhi, A.; Santulli, A.; Arena, R.; Bakhrouf, A.; Esteban, M.A.
Abstract: The present study was conducted to determine the potential effect of the dietary intake of fenugreek ( Trigonella foenum graecum ) seeds alone or in combination with Bacillus licheniformis, Lactobacillus plantarum or B. subtilis on gilthead seabream quality and antioxidant response after 2 and 3 weeks of experimental feeding. The results showed that the supplements did not affect the percentage of the fatty acid profiles of muscle, demonstrating that all the additives tested can be administrated without any negative effect on biochemical composition and quality of gilthead seabream. The quantification of thiobarbituric acid reactive substances in muscle demonstrated the significant beneficial effect of the experimental diets compared with the control one. Besides, an increase in superoxide dismutase and catalase in liver was recorded after 3 weeks of administration of experimental diets. Furthermore, real time qPCR revealed that dietary supplementation with FEBS significantly enhances the expression of scavenging enzymes, such as cat and gr genes in the liver after 3 weeks. The findings suggest that the administration of fenugreek supplement alone or combined with probiotic strains could be considered as a good source of natural antioxidants and as a functional aquafeed ingredient for gilthead seabream. Highlights: Antioxidant status of seabream after dietary fenugreek + probiotics was evaluated. Supplemented diets did not affect the fatty acid profiles of the muscle. Experimental diets showed antioxidant properties (decreased the TBARS in muscle). SOD and CAT were enhanced after fed experimental diets for 3 weeks. Fenugreek + probiotics up-regulated liver antioxidant-related gene expression.